Genome editing in Acinetobacter baumannii through enhanced natural transformation - Yilmaz, Ilknur; Ozbek, Tulin (WILEY-V C H VERLAG GMBH, 2024)
Acinetobacter baumannii, a multidrug-resistant bacterium has become a significant cause of life-threatening infections acquired in hospitals worldwide. The existing drugs used to treat A. baumannii infections are rapidly losing efficacy, and the increasing antimicrobial resistance, which is expected to turn into a global health crisis, underscores the urgency to develop novel prevention and treatment strategies. We reasoned that the discovery of novel virulence targets for vaccine and therapy interventions requires a more enhanced method for the introduction of multiple elements of foreign DNA for genome editing than the current methods of natural transformation techniques. Herein, we employed a novel and a much-improved enhanced technique for the natural transformation of elements of the genome editing system CRISPR-Cas9 to suppress specific genomic regions linked to selectively suppress bacterial virulence. We modified the genome of the laboratory-adapted strain of A. baumannii BAA-747 by targeting the AmpC, as a marker gene, for disruption by three different genomic manipulation strategies, and created mutant strains of A. baumannii that are, at least, fourfold susceptible to ampicillin. This work has established an optimized enhanced natural transformation system that enables efficient genome editing of pathogenic bacteria in a laboratory setting, providing a valuable future tool for exploring the function of unidentified virulence genes in bacterial genomes.
Keywords: Acinetobacter baumannii; AmpC gene; ampicillin; antibiotic resistance; CRISPR-Cas9; enhanced natural transformation; CRISPR-CAS; DNA UPTAKE; REPAIR; SYSTEM; Microbiology